Nucleotide sequence of the cDNA encoding the proenzyme of phenol oxidase A1 of Drosophila melanogaster. - Fujimoto, K (1995)
Clones encoding pro-phenol oxidase [pro-PO; zymogen of phenol oxidase (monophenol, L-dopa:oxygen oxidoreductase, EC 1.14.18.1)] A1 were isolated from a lambda gt10 library that originated from Drosophila melanogaster strain Oregon-R male adults. The 2294 bp of the cDNA included a 13-bp 5'-noncoding region, a 2070-bp encoding open reading frame of 690 amino acids, and a 211-bp 3'-noncoding region. A hydrophobic NH2-terminal sequence for a signal peptide is absent in the protein. Furthermore, there are six potential N-glycosylation sites in the sequence, but no amino sugar was detected in the purified protein by amino acid analysis, indicating the lack of an N-linked sugar chain. The potential copper-binding sites, amino acids 200-248 and 359-414, are highly homologous to the corresponding sites of hemocyanin of the tarantula Eurypelma californicum, the horseshoe crab Limulus polyphemus, and the spiny lobster Panulirus interruptus. On the basis of the phylogenetic tree constructed by the neighbor-joining method, vertebrate tyrosinases and molluscan hemocyanins constitute one family, whereas pro-POs and arthropod hemocyanins group with another family. It seems, therefore, likely that pro-PO originates from a common ancestor with arthropod hemocyanins, independently to the vertebrate and microbial tyrosinases.